Exploring the link between management training and organizational performance in the small business context. Issue 4 (27th March 2020) - Panagiotakopoulos, Antonios
Abstract : Purpose: This study aims to explore the impact of management training on organizational performance in the small business context to evaluate whether formal management learning interventions bring organizational benefits to small enterprises. Design/methodology/approach: A qualitative approach was adopted consisting of 100 interviews with small firm owners/managers and employees working in 50 Greek small enterprises operating in the manufacturing and services sectors. Participant firms consisted of 25 small enterprises (9 manufacturing firms and 16 firms in the services sector) whose owners/managers have completed various formal training interventions (i.e. accredited seminars and workshops, business and management courses, etc., ) and 25 small enterprises (16 manufacturing firms and 9 firms in the services sector) whose owners/managers have not completed any sort of formal business training and have never attended formal management courses. Findings: The findings revealed that management training in small businesses had a positive impact on organizational performance. In particular, those respondents that completed formal training interventions argued that their firms achieved increased profitability during 2017 and 2018; improved staff productivity; very low staff turnover rate; and enhanced staff satisfaction and motivation compared with the less-trained owners of small firms in the same sector. The participants pointed out that their formal education in business and management has enabled them to realize the importance of employee learning and job design for staff motivation, whereas it has helped them to manage change more effectively. Practical implications: The present findings have major implications for practitioners (i.e. small firm owners/managers), as they point to a positive link between management training and organizational performance, thus encouraging them to invest in their self-development. Originality/value: The existing evidence around the impact of management training on firm performance has been based mostly on quantitative research in large organizations. However, the available empirical studies fail to explore in-depth how formal management training can help smaller enterprises achieve improved organizational performance. Against this background, the present study sheds new light on this area.